Pengembangan Instrumen Penilaian Sikap Percaya Diri Siswa di Sekolah Dasar - Imroatun Khoiriyah; Samsi Haryanto; Rahayu Retnaningsih (Tuladha : Jurnal Pendidikan Dasar, 2022)
The purpose of this research is: (1) to find out how teachers evaluate students' self-confidence, (2) find out the form of instruments evaluating students' self-confidence, and (3) find out the tendency of students' self-confidence values. The results of this study indicate that, the teacher has not used the assessment sheet only uses observation sheets or journals to measure the value of students' self-confidence, the final instrument of self-confidence is valid and reliable with 8 indicators containing 40 items consisting of 20 valence items and 20 factual items , and resulted in the tendency of self-confidence of Elementary School Students of the Taruna Krida Group Sawangan District in medium category